An Unusual Coexistence of Ovarian Teratoma and Cholelithiasis in a Child: A Case Report - Yeshey Dorjey; Deep Kiran Chhetri; Tashi Gyeltshen (Clinical Case Reports)
ABSTRACT Ovarian tumors and cholelithiasis are uncommon in young children. The simultaneous occurrence of ovarian tumors and cholelithiasis in a child is extremely rare and has not been documented in the literature. This case report describes the first documented instance of a 5‐year‐old girl having both an ovarian teratoma and cholelithiasis. She was treated with laparoscopic ovarian cystectomy and laparoscopic cholecystectomy during the same surgical procedure.